2010
DOI: 10.1044/1092-4388(2009/09-0003)
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vocal Practice in Constructing Phonological Working Memory

Abstract: Performance depended on familiarity with words or their subunits and was strongest for real words, weaker for in words, and weakest for out words. The results demonstrate the important role of speech production in the construction of phonological working memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 32 publications
4
50
0
Order By: Relevance
“…Second, a perceptual CL bias might be more difficult to learn than a perceptual LC bias, because it goes against what appears to be a language-general production LC bias (which will however need to be further evaluated in future studies), as is suggested for Japanese by the adults data obtained by Tsuji et al (2012). These opposed production/perception biases might make the learning of these phonotactic dependencies more difficult, since several studies have shown the importance of the perception-production link (see Vihman, 1993;Vihman & Croft, 2007;Yeung & Werker, 2013) and the influence of production experience on infant speech processing (Keren-Portnoy, Vihman, DePaolis, Whitaker, & Williams, 2010;DePaolis, Vihman, & Keren-Portnoy, 2011;DePaolis, Vihman, & Nakai, 2013;Majorano, Vihman, & DePaolis, 2014). These different explanations are likely to be non-mutually exclusive, in particular in light of the fact that French-learning infants have been found to acquire a CL bias for fricative sequences without any developmental lag (e.g., by 10 months), a case that crucially differs from the present case in the fact that the input patterns were much clearer.…”
Section: Discussionmentioning
confidence: 89%
“…Second, a perceptual CL bias might be more difficult to learn than a perceptual LC bias, because it goes against what appears to be a language-general production LC bias (which will however need to be further evaluated in future studies), as is suggested for Japanese by the adults data obtained by Tsuji et al (2012). These opposed production/perception biases might make the learning of these phonotactic dependencies more difficult, since several studies have shown the importance of the perception-production link (see Vihman, 1993;Vihman & Croft, 2007;Yeung & Werker, 2013) and the influence of production experience on infant speech processing (Keren-Portnoy, Vihman, DePaolis, Whitaker, & Williams, 2010;DePaolis, Vihman, & Keren-Portnoy, 2011;DePaolis, Vihman, & Nakai, 2013;Majorano, Vihman, & DePaolis, 2014). These different explanations are likely to be non-mutually exclusive, in particular in light of the fact that French-learning infants have been found to acquire a CL bias for fricative sequences without any developmental lag (e.g., by 10 months), a case that crucially differs from the present case in the fact that the input patterns were much clearer.…”
Section: Discussionmentioning
confidence: 89%
“…Impaired phonological working memory (PWM) is thought to underlie speech and language difficulties because it underlies the creation of phonological representations [22]. Recent research, however, suggests that PWM is dependent upon the ability to assemble phonology for speech output [23]. Children were better able to repeat non-words that contained consonants and consonant combinations that they used frequently as opposed to non-words constructed of infrequently used consonant sequences.…”
Section: Associated Abilitiesmentioning
confidence: 96%
“…The impact of this link beyond the preference or dispreference for favorite consonants is an open question and should be explored further. For example, future work could examine how the relationship between production and perception affects the ability to attach meaning to word forms that either do or do not contain preferred production patterns (see Keren-Portnoy et al, 2010, for a study investigating phonological memory and preferred production patterns). Models could also incorporate proprioceptive feedback into the developmental trajectory of consonant and vowel categorization (for examples see models by Kent, 1981, andWestermann &Miranda, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…They found that the use of at least two VMS was a prerequisite for the transition into referential word use in the 20 children they observed. In the same way that self-produced locomotion facilitates the development of spatial awareness, the ability to produce consistent patterns in babble can be taken to support memory for word forms (Keren-Portnoy, Vihman, DePaolis, Whitaker, & Williams, 2010), which in turn facilitates the recognition that a word form can symbolize events or entities in the world.…”
Section: Introductionmentioning
confidence: 99%